2020
DOI: 10.3390/agronomy10050673
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Species and Cultivation Year on Phenolic Acids Content in Ancient Wheat

Abstract: During the last decade older (ancient) wheat species, such as spelt (Triticum spelta L.), emmer (Triticum dicoccon Schrank), and einkorn (Triticum monococcum L.) have been recognised as an interesting option to increase the biodiversity of cultivated cereals. The aim of this study was to compare polyphenols content in the ancient species of cereals (including six accessions of spelt, four of emmer, and one of einkorn) cultivated in the three-year controlled plot experiment under organic management. It has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 43 publications
(68 reference statements)
3
12
1
Order By: Relevance
“…Wheat genotypes were reported to affect phenolic acid content and in vitro antioxidant capacity of whole wheat flour (Li et al., 2008). Effect of growth year on wheat phenolics and the year (Y) x variety (V) interactions has been also described in previous studies (Barański et al., 2020; Fernandez‐Orozco et al., 2010; Gasztonyi et al., 2011).…”
Section: Introductionsupporting
confidence: 72%
“…Wheat genotypes were reported to affect phenolic acid content and in vitro antioxidant capacity of whole wheat flour (Li et al., 2008). Effect of growth year on wheat phenolics and the year (Y) x variety (V) interactions has been also described in previous studies (Barański et al., 2020; Fernandez‐Orozco et al., 2010; Gasztonyi et al., 2011).…”
Section: Introductionsupporting
confidence: 72%
“…Wholegrain Triticum seeds are an excellent source of bound phenolic acids (which represent >90% of the total phenolic acids), followed by bound flavonoids and other phenolics [2,4,7,[29][30][31]. As reported by Balli et al [32], the hydrolysis conditions can significantly affect the total amounts and profile of the bound phenolics than can be extracted.…”
Section: Effects Of the Extraction Parameters On Bound Phenolicsmentioning
confidence: 99%
“…Over the past few decades, it has attracted renewed interest as a healthier, more natural, less 'over-bred' cereal compared to modern common wheat (Triticum aestivum L.). More recently, this has been combined with increased attention on the phenolics in the whole grain of Triticum species [1][2][3]. Our previous study suggested that germination of spelt seeds under specific combined stress conditions can significantly improve their total phenolics content (TPC), along with the levels of the individual phenolics and their scavenging activities against different free radicals (e.g., DPPH • , ABTS •+ , O 2…”
Section: Introductionmentioning
confidence: 99%
“…Total phenolic content of flour methanolic extracts were higher in the two ancient wheat cultivar and led to a higher antioxidant capacity, hence improving their overall nutritional quality. Whole wheat flours are generally rich in phenolic acids, however their biosynthesis and accumulation strongly depends on both variety and environmental conditions [24,25].…”
Section: Flour Characterizationmentioning
confidence: 99%